THE IMPORTANCE OF DIGITAL TECHNOLOGIES, ARTIFICIAL INTELLIGENCE, AND MATHEMATICAL METHODS IN THE EDUCATION SYSTEM - Ibragimov Zoyirjon Ziyatovich; Ibragimova Nargiza Anorovna (Uzbekistan Open Conference, 2026)
This article examines the role of digital technologies, artificial intelligence, and mathematical methods in the modern education system. It analyzes the impact of these technologies on improving the quality of education, personalizing the learning process, and developing intelligent educational systems. Special attention is given to the importance of mathematical methods as the foundation of artificial intelligence algorithms that enable the processing and analysis of educational data. It is shown that the integration of digital technologies and mathematical modeling contributes to the creation of an efficient, adaptive, and innovative educational environment.
Keywords: digital technologies; artificial intelligence; education; mathematical methods; adaptive learning; educational data; digital transformation; personalization